Low Salt Delivery Triggers Autocrine Release of Prostaglandin E2 From the Aldosterone-Sensitive Distal Nephron in Familial Hyperkalemic Hypertension Mice - Zapf, Ava M.; Grimm, Paul R.; Al-Qusairi, Lama; Delpire, Eric; Welling, Paul A. (Frontiers in Physiology, 2022)
Aberrant activation of WNK-SPAK kinase signaling in the distal convoluted tubule (DCT) causes unbridled activation of the thiazide-sensitive sodium chloride cotransporter, NCC, leading to Familial Hyperkalemic Hypertension (FHHt) in humans. Studies in FHHt mice engineered to constitutively activate SPAK specifically in the DCT (CA-SPAK mice) revealed maladaptive remodeling of the aldosterone sensitive distal nephron (ASDN), characterized by decrease in the potassium excretory channel, ROMK, and ENaC, that contributes to the hyperkalemia. The mechanisms by which NCC activation in DCT promotes remodeling of CNT are unknown, but paracrine communication and reduced salt delivery to the ASDN have been suspected. Here we explore the involvement of prostaglandin E2 (PGE2). We found that PGE2 and the terminal PGE2 synthase, mPGES1, are increased in kidney cortex of CA-SPAK mice, compared to control or SPAK KO mice. Hydrochlorothiazide (HCTZ) reduced PGE2 to control levels, indicating increased PGE2 synthesis is dependent on increased NCC activity. Immunolocalization studies revealed mPGES1 is selectively increased in the connecting tubule of CA-SPAK mice, implicating low salt-delivery to ASDN as the trigger. Salt titration studies in an in vitro ASDN cell model, mCCD-CL1, confirmed PGE2 synthesis is activated by low salt, and revealed that response is paralleled by induction of mPGES1 gene expression. Finally, inhibition of the PGE2 receptor, EP1, in CA-SPAK mice partially restored potassium homeostasis as it partially rescued ROMK protein abundance, but not ENaC. Together, these data indicate low sodium delivery to the ASDN activates PGE2 synthesis and this inhibits ROMK through autocrine activation of the EP1 receptor. These findings provide new insights into the mechanism by which activation of sodium transport in the DCT causes remodeling of the ASDN.